Wheelchair propulsion kinematics in beginners and expert users: Influence of wheelchair settings - Gorce, P.; Louis, N. (Clinical Biomechanics, 2012)
Biomechanical studies have linked the handrim wheelchair propulsion with a prevalence of upper limb musculoskeletal disorders. The purpose of this study was to examine the influence of the wheelchair settings on upper limb kinematics during wheelchair propulsion. Recordings were made under various wheelchair configuration conditions to understand the effect of wheelchair settings on kinematics parameters such shoulder, elbow and wrist angles. Methods Ten experts and ten beginners` subjects propelled an experimental wheelchair on a roller ergometer system at a comfortable speed. Twelve wheelchair configurations were tested. Kinematics were recorded for each configuration. Based on the hand position relatively to the handrim, the main kinematic parameters of wheelchair propulsion were investigated on the whole propulsion cycle and a key event such as handrim contact and release.